Serial Sovereign Defaults and Debt Restructurings - Asonuma, Tamon (IMF Working Papers; Working Paper ;, 2016)
Emerging countries that have defaulted on their debt repayment obligations in the past are more likely to default again in the future than are non-defaulters even with the same external debt-to-GDP ratio. These countries actually have repeated defaults or restructurings in short periods. This paper explains these stylized facts within a dynamic stochastic general equilibrium framework by explicitly modeling renegotiations between a defaulting country and its creditors. The quantitative analysis of the model reveals that the equilibrium probability of default for a given debt-to-GDP level is weakly increasing with the number of past defaults. The model also accords with an additional fact: lower recovery rates (high NPV haircuts) are associated with increases in spreads at renegotiation.